The health behaviors and their selected predictors vs. the quality of women`s life in perimenopausal period on the example of women addicted to alcohol - Banaszkiewicz, Mariola; Ciecieląg, Anna; Andruszkiewicz, Anna; Betke, Katarzyna; Marzec, Alicja (Nursing in the 21st Century, 2015)
THE HEALTH BEHAVIORS AND THEIR SELECTED PREDICTORS VS. THE QUALITY OF WOMEN`S LIFE IN PERIMENOPAUSAL PERIOD ON THE EXAMPLE OF WOMEN ADDICTED TO ALCOHOL Introduction. The hormonal changes in a woman’s body can unfavorably affect the functioning of each sphere of her life. Some women reach for alcohol to relieve unpleasant symptoms related to that period and consequently become addicted to alcohol. Aim. The aim of the study was to demonstrate the relationship between the selected predictors, such as: a sense of coherence and its components, control of emotions, self-efficacy and health-related behavior and quality of life of the examined perimenopausal women addicted to alcohol. Material and methods. The study was conducted using the following survey research tools: a Sense of Coherence-Orientation to Life Questionnaire (SOC-29), and gynecological history, Courtland Emotional Control Scale (CESC), health behavior scale for women (SZZK), Generalized Self-Efficacy Scale (GSES), a standardized test of the quality of life (EQ-5D). The study involved 50 perimenopausal women with alcohol dependence aged 40-55 years – the participants of the AA meetings. The study was conducted throughout January-April 2013. Results. Statistical analysis showed the relationship between an overall sense of coherence with all subscales of health behaviors in the examined women. The higher level of sense of coherence, the higher scores on the scales of health behaviors. The analysis of the results showed the relationship between selected predictors of coherence and its components, control of emotions, self-efficacy and quality of life of the respondents. Conclusion. Sense of coherence and its components, self-efficacy and control of emotions (anger) proved to be the predictors of health behavior and quality of life of perimenopausal women addicted to alcohol. In the educational activities undertaken by an interdisciplinary team, the above-mentioned resources should be taken into account.